Integrasi Pendekatan STEM dalam Pembelajaran IPA untuk Mengembangkan Kreativitas dan Pemecahan Masalah Siswa di SMPN 1 Cigombong - Eva Mulida Hazana (Universitas Palangka Raya, 2025)
This study aims to analyze the effect of integrating the STEM (Science, Technology, Engineering, Mathematics) approach in science education on students' creativity and problem-solving abilities at SMPN 1 Cigombong. The STEM approach was implemented to provide an integrated learning experience, allowing students to connect science concepts with technology, engineering, and mathematics. The research method used is classroom action research (CAR), conducted in two cycles, with observation, tests, and interviews as instruments for data collection. The results showed that the implementation of the STEM approach improved students' creativity and problem-solving skills, as well as facilitated students in applying science concepts in daily life. Furthermore, students also demonstrated an increase in collaboration and communication skills. These findings contribute to the development of more relevant learning methods that meet the demands of 21st-century education in secondary schools.